2019
DOI: 10.1002/advs.201802042
|View full text |Cite
|
Sign up to set email alerts
|

TLR1/2 Specific Small‐Molecule Agonist Suppresses Leukemia Cancer Cell Growth by Stimulating Cytotoxic T Lymphocytes

Abstract: Toll‐like receptor 2 (TLR2) expressed on antigen presenting cells evokes a series of critical cytokines, which favor the development of tumor‐specific cytotoxic T lymphocytes (CTLs). Therefore, TLR2 represents an attractive cancer immunotherapeutic target. Here, a synthetic library of 14 000 compounds together with a series of newly developed compounds for NF‐κB activation using HEK‐Blue hTLR2 cells is initially screened. Following further screening in a variety of cells including HEK‐Blue hTLRs reporter cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…42 43 Here, in tumor-bearing mice, it was first found that tumor suppression efficacy of Amuc was partly mediated through TLR2 signaling pathway, which is consistent with other reports that activation of TLR2 was capable of remodeling tumor immune microenvironment and, in turn, inducing significant tumor shrink. [44][45][46][47][48] In addition, our results are also in line with the previous studies that Amuc could specially stimulate ex vivo TLR2expressing cells to prevent the development of obesity and type 2 diabetes. 24 As an active part of AKK to produce antitumor effects, Amuc can also be used as a potential adjuvant for cancer immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…42 43 Here, in tumor-bearing mice, it was first found that tumor suppression efficacy of Amuc was partly mediated through TLR2 signaling pathway, which is consistent with other reports that activation of TLR2 was capable of remodeling tumor immune microenvironment and, in turn, inducing significant tumor shrink. [44][45][46][47][48] In addition, our results are also in line with the previous studies that Amuc could specially stimulate ex vivo TLR2expressing cells to prevent the development of obesity and type 2 diabetes. 24 As an active part of AKK to produce antitumor effects, Amuc can also be used as a potential adjuvant for cancer immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…The quantitative relationship between the spatial arrangement of Pam 3 nanodisks and macrophage immune responses we found in this study indicates that it is possible to modulate immune responses by engineering the spatial organization of cell receptors. Recent studies have shown potential applications of Pam 3 ( 61 ) and other TLR1/2 agonists ( 62 64 ) as adjuvants for tumor immunotherapy. It was suggested that coactivation of TLR1/2 together with FcRs may provide the strong pro-inflammatory responses needed to reverse the tumor immunosuppressive environment in antibody-based cancer immunotherapy ( 20 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by animal TLR knockout models [ 90 , 91 , 92 , 93 , 94 , 95 , 96 ] and studies involving TLR deficiency [ 97 , 98 ] and polymorphisms in humans [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ], absence or improper function of TLRs can attenuate inflammation, influence disease susceptibility, and restore homeostatic balance. Thus, TLRs have become targets of TLR inhibition therapies [ 112 , 113 , 114 , 115 , 116 ]. This review will discuss the potential inhibitory and immunomodulating abilities of taurine and its metabolites on TLR signal transduction, which may make them suitable anti-inflammatory therapeutics in CVD pathologies.…”
Section: Taurine the Innate Immune System And Potential Therapeumentioning
confidence: 99%
“…Deficiencies and polymorphisms have shown beneficial results in disease severity and susceptibility [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Thus, TLRs have become targets of pharmaceuticals and small molecules treatments in TLR inhibition therapies [ 112 , 113 , 114 , 115 , 116 ]. TLRs exert damaging effects through chronic unregulated inflammation through the TLR/MyD88/NF- K pathway [ 80 ].…”
Section: Taurine the Innate Immune System And Potential Therapeumentioning
confidence: 99%